Phenotypic Profiling of Biofilm Development and Efflux Pump Mechanisms in Multidrug-Resistant (MDR) Klebsiella pneumoniae - Hadiza Na`'iya Misbahu; Abdulhamid Yusuf; Zahra Na`'iya Misbahu; Dikwa, K. B.; Shafa'atu Abubakar; Bilkisu Isma'il; Fadila Isyaku; Adeleye Adewale Isaac (UMYU Journal of Microbiology Research, 2025)
Study’s Excerpt: